ΔPCO2 and ΔPCO2/C(a−cv)O2 Are Not Predictive of Organ Dysfunction After Cardiopulmonary Bypass - Zhang, Sheng; Zheng, Dan; Chu, Xiao-Qiong; Jiang, Yong-Po; Wang, Chun-Guo; Zhang, Qiao-Min; Qian, Lin-Zhu; Yang, Wei-Ying; Zhang, Wen-Yuan; Tung, Tao-Hsin; Lin, Rong-Hai (Frontiers in Cardiovascular Medicine, 2021)
Background: Cardiac surgery is associated with a substantial risk of major adverse events. Although carbon dioxide (CO2)-derived variables such as venous-to-arterial CO2 difference (ΔPCO2), and PCO2 gap to arterial–venous O2 content difference ratio (ΔPCO2/C(a−cv)O2) have been successfully used to predict the prognosis of non-cardiac surgery, their prognostic value after cardiopulmonary bypass (CPB) remains controversial. This hospital-based study explored the relationship between ΔPCO2, ΔPCO2/C(a−cv)O2 and organ dysfunction after CPB. Methods: We prospectively enrolled 114 intensive care unit patients after elective cardiac surgery with CPB. Patients were divided into the organ dysfunction group (OI) and non-organ dysfunction group (n-OI) depending on whether organ dysfunction occurred or not at 48 h after CPB. ΔPCO2 was defined as the difference between central venous and arterial CO2 partial pressure. Results: The OI group has 37 (32.5%) patients, 27 of which (23.7%) had one organ dysfunction and 10 (8.8%) had two or more organ dysfunctions. No statistical significance was found (P = 0.84) for ΔPCO2 in the n-OI group at intensive care unit (ICU) admission (9.0, 7.0–11.0 mmHg), and at 4 (9.0, 7.0–11.0 mmHg), 8 (9.0, 7.0–11.0 mmHg), and 12 h post admission (9.0, 7.0–11.0 mmHg). In the OI group, ΔPCO2 also showed the same trend [ICU admission (9.0, 8.0–12.8 mmHg) and 4 (10.0, 7.0–11.0 mmHg), 8 (10.0, 8.5–12.5 mmHg), and 12 h post admission (9.0, 7.3–11.0 mmHg), P = 0.37]. No statistical difference was found for ΔPCO2/C(a−cv)O2 in the n-OI group (P = 0.46) and OI group (P = 0.39). No difference was detected in ΔPCO2, ΔPCO2/C(a−cv)O2 between groups during the first 12 h after admission (P > 0.05). Subgroup analysis of the patients with two or more failing organs compared to the n-OI group showed that the predictive performance of lactate and Base excess (BE) improved, but not of ΔPCO2 and ΔPCO2/C(a−cv)O2. Regression analysis showed that the BE at 8 h after admission (odds ratio = 1.37, 95%CI: 1.08–1.74, P = 0.009) was a risk factor for organ dysfunction 48 h after CBP. Conclusion : ΔPCO2 and ΔPCO2/C(a−cv)O2 cannot be used as reliable indicators to predict the occurrence of organ dysfunction at 48 h after CBP due to the pathophysiological process that occurs after CBP.